Functional Damage Assessment Method for Preformed Fragment Warheads to Evaluate the Effect on the Phased-Array Antenna - Zou, Shaoxin; Gu, Wenbin; Ren, Wen; Shen, Chaohu; Chen, Zhaoyi; Hao, Likai (Electronics (Basel), 2023)
Damage assessment of a small-weight precision-guided warhead to evaluate the effect on the performance of high-value vulnerable targets should focus on functional damage instead of physical damage. Developing a damage assessment model that considers target function attenuation as a damage criterion for warhead design and tactical application is of great significance. In this paper, an accurate mathematical description of a preformed fragment warhead is provided. The failure of phased-array antenna elements in different initiation conditions is predicted by a shot-line model and spatial coordinate mapping. A real-time co-simulation model of the explosion damage field and the phased-array antenna electrical performance is developed and the effective damage modes are obtained through multi-condition simulation and electrical performance parameters analysis, which has more tactical application value than the structural damage assessment method with equivalent targets and the electrical simulation in artificial or random phrased-array-element failure conditions.